Experiencing death: an insider's perspective. (24th July 2014) - Paulson, Steve; Fenwick, Peter; Neal, Mary; Nelson, Kevin; Parnia, Sam
Abstract : For millennia, human beings have wondered what happens after death. What is the first‐person experience of dying and being brought back to life? Technological advances in resuscitation science have now added an intriguing new chapter to the literature of out‐of‐body or near‐death experiences by eliciting detailed and vivid accounts of those who have approached the threshold of death. Steve Paulson, executive producer and host of To the Best of Our Knowledge, moderated a discussion that included neurologist Kevin Nelson, neuropsychiatrist Peter Fenwick, emergency medicine expert Sam Parnia, and orthopedic surgeon and drowning survivor Mary Neal; they share some remarkable stories and discuss how they analyze such experiences in light of their own backgrounds and training. The following is an edited transcript of the discussion from December 11, 2013, 7:00–8:30 PM, at the New York Academy of Sciences in New York City.